Rekayasa Traffic Jaringan pada Protokol Destination Sequenced Distance Vector (DSDV) berdasarkan Penggunaan Energi dalam MANET - Muhammad Ryan Firmansyah; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
MANET is a wireless network architecture where nodes can move freely and do not need to be connected to infrastructure. In MANET, all nodes act as a host and router that can receive and send data packets to other nodes. In addition, MANET also has limitation in energy usage. Nodes require sufficient energy resources when transmitting data packets. However, when the energy in the battery has been or will be depleted, that will cause process of data packet transmission to be disrupted. Therefore, limiting on energy usage are needed so data packets can be transmitted. The example protocol in MANET is Destination Sequenced Distance Vector (DSDV). By using the energy model contained in NS-3.30.1, DSDV protocol is integrated with the energy model in order to read the remaining energy during the data packet transmission process. There are two schemes; (1) Scheme without Traffic Engineering and (2) Scheme with Traffic Engineering tested. Traffic Engineering that is built is limiting the data packets that can be forwarded based on an energy level of 500 Joules. The results show that the scheme with Traffic Engineering saving energy usage in each number of nodes with a percentage are 0,112%, 0,03% and 0,033% whereas the highest Packet Delivery Ratio (PDR) value is all schemes without Traffic Engineering.